THE LEVEL OF COMPLIANCE OF HEALTHCARE WORKERS IN PERFORMING HAND HYGIENE: A LITERATURE REVIEW - Selvia Rahayu; F Sri Susilaningsih; Maria Komariah (Universitas Padjadjaran, 2021)
Compliance level of healthcare workers in performing hand hygiene is a significant aspect of patient safety goals. However, it is still not optimal and is one of the critical problems of many hospitals globally, including in Indonesia. The non-optimal consequence of hand hygiene compliance is hospital-associated infections since hands are an intermediary medium for transmitting infection. This literature aims to determine the level of compliance of health workers in performing hand hygiene and find out several matters that can be done so that the health worker's compliance can be optimal or increased. Review of articles through several electronic databases including PubMed and ProQuest, with the keywords